2015
DOI: 10.5194/acpd-15-15791-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

16 year climatology of cirrus clouds over a tropical station in southern India using ground and space-based lidar observations

Abstract: Abstract. 16 year (1998–2013) climatology of cirrus clouds and their macrophysical (base height, top height and geometrical thickness) and optical properties (cloud optical thickness) observed using a ground-based lidar over Gadanki (13.5° N, 79.2° E), India, is presented. The climatology obtained from the ground-based lidar is compared with the climatology obtained from seven and half years (June 2006–December 2013) of Cloud-Aerosol LIdar with Orthogonal Polarization (CALIOP) observations. A very good agreeme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…16-year climatological assessment of cirrus clouds, their microphysical, and optical properties were observed using a ground-based lidar over Gadanki, India (Pandit et al, 2015). When compared with those obtained by CALIOP, the observations showed the presence of cirrus clouds of geometrical thickness less than 2 km.…”
Section: Convective Influencementioning
confidence: 98%
See 1 more Smart Citation
“…16-year climatological assessment of cirrus clouds, their microphysical, and optical properties were observed using a ground-based lidar over Gadanki, India (Pandit et al, 2015). When compared with those obtained by CALIOP, the observations showed the presence of cirrus clouds of geometrical thickness less than 2 km.…”
Section: Convective Influencementioning
confidence: 98%
“…When compared with those obtained by CALIOP, the observations showed the presence of cirrus clouds of geometrical thickness less than 2 km. Moreover, the increasing fraction of sub-visible cirrus clouds between 1998-2003 probably modified on the temperature and the water vapor budget in the Tropical Tropopause Layer (Pandit et al, 2015). To study the impact of convection on our measurements, we calculate back-trajectories from ZF2 and ZF3 using the Langley Trajectory Model (LaTM) driven by GEOS-5 winds (Fairlie et al, 2014) and locate the intersection with anvils and deep convective clouds observed through Cloud Top Brightness Temperature from the HIMAWARI-8 satellite (Vernier et al, 2018).…”
Section: Convective Influencementioning
confidence: 99%